Solvent‐Based and Matrix‐Matched Calibration Methods on Analysis of Ceftiofur Residues in Milk and Pharmaceutical Samples Using a Novel HPLC Method - Saniye Özcan; Serkan Levent; Nafiz Öncü Can (Veterinary Medicine and Science)
ABSTRACT Background The matrix effect is accepted as one of the critical factors that affect trueness, and it is especially important in the analysis of critical compounds, such as drugs, toxins and pesticides, in complex matrices. Ceftiofur (CEF) is a leading drug used in dairy industry for pulmonary infections. Because milk has a complex matrix, which is rich in fats, proteins and many other compounds, the determination of CEF in milk products deals with issues of trueness. On the other hand, pharmaceuticals also have a complex composition as they contain not only the active pharmaceutical ingredient but also many excipients, such as preservatives and pH modifiers. Due to its frequent use, its residues can be found in meat products or exist as an excreted compound in urine, milk and so on. Objective The aim of this study was to investigate the effect of different calibration methods on quantitative estimation of CEF in milk and pharmaceutical samples. Methods CEF was analysed using a new HPLC method, in which separation was achieved on a C18 bonded fused‐core silica particle column by using isocratic elution; the method was optimized by testing different chromatographic conditions and validated according to the ICH Q2(R1) and United States Pharmacopeia guidelines. Results Interestingly, it was found that CEF signals in milk samples were higher than the ones at the same level prepared in calibration solutions with a ratio of 11.28:1. Conclusion This finding reveals the necessity of matrix‐matched calibration for accurate quantitative determination of CEF in milk samples. Moreover, the milk in the market and the most used pharmaceutical formulations were analysed using the current method.